Media Interaktif berbasis Animasi pada Pembelajaran Tari - Hary Murcahyanto; Linda Laili Harjuni; Mohzana Mohzana (Jurnal Pendidikan Informatika (EDUMATIC), 2022)
Learning arts and culture, especially dance in this digital era, really needs learning media that are appropriate to the situation and conditions. The interactive media required at this time are animation-based media because these demands are the media that are preferred by students and are considered the most fun. This study aims to analyze the development of audio-visual media animation in dance learning and its development effectiveness. The method used in developing the Borg and Gall model includes needing analysis, design planning, product development, product revision, and field trials to the results using Macromedia Flash 8 media. The instruments used to collect data in this study were questionnaires, interview guidelines, and observations at SMAN 1 Labuhan Haji, East Lombok. These findings We are in the form of learning media based on audiovisual animation using Macromedia Flash 8 through a complete process and feasibility test so that it is easy to use. The feasibility of the developed press, based on tests from media experts, obtained good criteria (GC), material experts obtained GC criteria, and user tests obtained perfect criteria.